Legalization of Medical Cannabis: Indonesia’s Regulatory Framework and Lessons from Thailand - Tiya Yolanda Nur Fadhila, Gusti; Lewoleba, Kayus Kayowuan (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the prospects of legalizing cannabis for medical use in Indonesia through a comparative study with the policies implemented in Thailand. The method used is normative-empirical legal research, combining literature review (legislation and literature) with in-depth interviews with the National Narcotics Agency and Lingkar Ganja Nusantara to enrich and validate normative findings. The results of the study show that the potential for medical cannabis legalization in Indonesia is highly dependent on the implementation of strict and structured regulations, an effective monitoring system, and a phased approach. The comparative study with Thailand provides crucial lessons on the need for a mature legal framework and strong control mechanisms to avoid the risks of uncontrolled liberalization. The novel contribution of this research lies in the integration of empirical perspectives from key actors in analyzing lessons learned from Thailand to formulate an adaptive policy model in Indonesia. Thus, this study concludes that the legalization of medical cannabis in Indonesia has great prospects for realization, provided it is supported by comprehensive policies that prioritize public health interests and legal certainty.